Treadmilling Model for Plasticity of the Myelin Sheath - Fields, R. Douglas (Trends Neurosci, 2019)
We propose a mechanism for myelin plasticity that would complement synaptic plasticity by adjusting conduction velocity for optimal spike-time arrival. In the proposed treadmilling model, myelin sheath thickness is a dynamic balance between the rates of new myelin deposited adjacent to the axon and removal of the outermost layer.